IDENTIFICATION OF GROUNDWATER POTENTIAL USING GEOGRAPHIC INFORMATION SYSTEMS AND REMOTE SENSING (CASE STUDY: MOJOKERTO REGENCY) - Sulle, Beata Alpha Christina; Sunaryo, Dedy Kurnia; Yulianandha, Adkha (Journal of Marine-Earth Science and Technology, 2023)
The impact of the drought problem in Mojokerto Regency resulted in thousands of people having access to clean water. So, it is necessary to plan the utilization of groundwater resources well. Therefore, more serious handling is needed in an effort to overcome the problem of groundwater supply. One of them is the availability of groundwater potential maps. This study aims to determine the identification of aquifer potential and groundwater potential in Mojokerto Regen cy in 2020. This research uses SPO T - 7 satellite imagery to see vegetation density using the NDVI method and uses 5 parameters, namely rainfall, soil texture, rock type/geology, slope, and land use. This study used the AHP method in determining the priority weight value of each parameter. Based on the results of the study, the results were obtained with 3 classifications with the largest area being an area with mode rate groundwater potential of 52,621.285 Ha and the smallest area being an area with low groundwater potential of 2,426.327 Ha. Previous research identified groundwater potential using the NDVI method with Landsat 8 imagery which has a resolution of 30 meters. Therefore, this research is expected to produce better vegetation density by using SPOT-7 imagery to obtain more detailed groundwater potential, because the resolution of the image SPO T -7 is 6 meters. So that this research can be considered in efforts to process the potential of groundwater resources in Mojokerto Regency